Enterprise Architecture Design for the Electronic-Based Government System (SPBE) at the East Kalimantan Housing and Settlement Office Using the TOGAF ADM Framework - Eko Junirianto; Agustinus Frizt WIjaya; Desi Pujiati; Dewi Safitriani; Reza Andrea (Journal of Information System and Informatics, 2026)
The Electronic-Based Government System (SPBE) is a central component of Indonesia's digital governance strategy. At the East Kalimantan Housing and Settlement Office (Disperkim), the quality index of residential areas has persistently failed to reach its annual target, indicating fragmented information system use and structural inefficiencies in managing infrastructure, facilities, and public utilities (PSU) services. This study proposes an enterprise architecture design based on the TOGAF ADM framework to address this gap. Employing an architectural design research approach, the study collected primary data through semi-structured interviews with five Disperkim stakeholders and secondary data from Presidential Regulation No. 95 of 2018 on SPBE. The resulting blueprint covers four domains, business, data, application, and technology, and is aligned with organizational performance indicators and regulatory requirements. A key contribution is the proposed integration of the Sakti Gemas mobile application as a centralized public service platform that is expected to support more responsive PSU service delivery. The proposed architecture was validated at the design level through a Focused Group Discussion (FGD) with key Disperkim stakeholders, confirming its contextual appropriateness and technical feasibility. No implementation or quantitative service-performance evaluation has been conducted; operational impact can only be measured after system deployment. This study contributes a replicable architectural model for improving digital governance effectiveness in similar regional government institutions.